How Does Adding the DSM-5 Criterion Increased Energy/Activity for Mania Change the Bipolar Landscape? - Grunze, Anna; Born, Christoph; Fredskild, Mette U.; Grunze, Heinz (Frontiers in Psychiatry, 2021)
According to DSM-IV, the criterion (A) for diagnosing hypomanic/manic episodes is mood change (i.e., elevated, expansive or irritable mood). Criterion (A) was redefined in DSM-5 in 2013, adding increased energy/activity in addition to mood change. This paper examines a potential change of prevalence data for bipolar I or II when adding increased energy/activity to the criterion (A) for the diagnosis of hypomania/mania. Own research suggests that the prevalence of manic/hypomanic episodes drops by at least one third when using DSM-5 criteria. Whether this has positive or negative impact on clinical practice and research still needs further evaluation.